Meaning of the Phrase 'Worship Him Faithfully' and the Application of Congregational Presence in Worship at GBI Taman Permata - Ngguna, Apriyani Rambu; Lumingkewas, Marthin Steven (Indonesian Journal of Religious, 2024)
This study explores the understanding and practice of worship within the congregation of GBI Taman Permata, focusing on the phrase "worship Him faithfully." The research reveals that a deeper comprehension of worship leads to increased participation in church activities and a stronger commitment to regular worship. Using a qualitative approach, data was collected through literature review and interviews with members of the congregation. The findings suggest that worship, when understood as a personal and relational act rather than a ritualistic obligation, fosters spiritual growth and enhances community engagement. The study also highlights the transformative power of worship in shaping the spiritual lives of the believers, contributing to both personal and communal transformation.   Contribution: This study contributes to the understanding of how theological insights into worship influence congregational commitment and engagement in church life. It also highlights the role of worship in fostering spiritual growth and strengthening church community bonds.